Extensive Idiopathic External Root Resorption in First Maxillary Molar: A Case Report - Bolhari, Behnam; Meraji, Naghmeh; Nosrat, Ali (Iranian Endodontic Journal, 2013)
External root resorption of permanent teeth is a multifactorial process. Several etiologic and predisposing factors have been related to external root resorption. Idiopathic external root resorption is defined as cases of external root resorption without a distinct etiologic factor. This article presents an extensive idiopathic external root resorption of maxillary first molar with irreversible pulpitis in an 18-year-old patient. The resorption was diagnosed in conventional radiographs and confirmed with Cone Beam Computed Tomography (CBCT) images. Unlike other reports in this field, and despite the severe resorption of all roots, there was no abnormal tooth mobility. Cold and electric pulp tests confirmed tooth vitality and revealed irreversible pulpitis. Therefore the exact etiology of the resorption remained unclear. Considering the poor prognosis due to severe root resorption, extraction and implant replacement was indicated.